2021
DOI: 10.3390/app112411939
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Effect on Fatigue Behaviour of Notched Carbon/Epoxy Laminates

Abstract: This paper studies the effect of seawater immersion on the fatigue behavior of notched carbon/epoxy laminates. Rectangular cross-section specimens with a central hole were immersed in natural and artificial seawater for different immersion times (0, 30 and 60 days), being the water absorption rate evaluated over time. After that, fatigue tests were performed under uniaxial cyclic loading using a stress ratio equal to 0.1. After the tests, the optical microscopy technique allowed the examination of the failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Fatigue life predictions revealed that, for 10 7 cycles, basalt/epoxy composites aged in seawater for 6 weeks would undergo a reduction of 11% concerning the maximum applied stress [87]. Notched carbon/epoxy laminates-rectangular cross-sections with a central hole-suffered dire repercussions subsequent to immersion in natural and artificial seawater for 30 and 60 days in their low-cycle fatigue behaviour-for 10 4 cycles, the stress amplitude was 1.2 times higher for dry laminates [88]. Still, no discernible differences were observed in the fatigue behaviour regarding the immersion duration or the type of seawater and for high-cycle fatigue, the lifetime of the laminates was not affected-superior impact of holes and respective induced stress concentrations.…”
Section: Seawatermentioning
confidence: 99%
“…Fatigue life predictions revealed that, for 10 7 cycles, basalt/epoxy composites aged in seawater for 6 weeks would undergo a reduction of 11% concerning the maximum applied stress [87]. Notched carbon/epoxy laminates-rectangular cross-sections with a central hole-suffered dire repercussions subsequent to immersion in natural and artificial seawater for 30 and 60 days in their low-cycle fatigue behaviour-for 10 4 cycles, the stress amplitude was 1.2 times higher for dry laminates [88]. Still, no discernible differences were observed in the fatigue behaviour regarding the immersion duration or the type of seawater and for high-cycle fatigue, the lifetime of the laminates was not affected-superior impact of holes and respective induced stress concentrations.…”
Section: Seawatermentioning
confidence: 99%
“…[1][2][3] The performance degradation of composite structural parts subjected to the marine environment has become a major concern. [4][5][6] The integrity of the composites can be negatively affected in the marine environment. Studies have shown that the impact performance, 7 bending strength, 8 tensile strength, 9 fracture toughness, 10 and other mechanical properties of laminated and woven composites subjected to marine environments can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted to evaluate the effects of hostile environments on composite materials [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The absorption of water is detrimental to the mechanical properties of FRP composites, since it affects the resin matrix by plasticization and also deteriorates the matrix–fiber interface [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%